Effect of Mechanical Milling on the Total Phenolic Content and Antioxidant Activity of Garcinia mangostana Pericarp - Nugroho, Dwi Wahyu; Daratika, Dyah Ayu; Kamila, Muthia; Togatorop, Lusiana; Rifada, Mohammad Aulia; Widayatno, Wahyu Bambang; Maulana, Syahrizal; Setyawati, Damai Ria; Mardliyati, Etik; Rochman, Nurul Taufiqu (Makara Journal of Science, 2020)
This study aimed to identify the effect of mechanical milling on the total phenolic content and antioxidant activity of mangosteen pericarp. Mangosteen pericarp was milled under different milling times (30, 90, 150, and 210 min). The particle morphology before and after milling was observed by scanning electron microscopy (SEM), and the average particle size was obtained from SEM images and analyzed statistically. The antioxidant activity was measured through the 2,2-diphenyl-1-picrylhydrazyl method. The total phenolic content for the non-milling sample was 14.52 × 104 µg GAE/g sample, and the highest total phenol content was 17.44 × 104 µg GAE/g sample for the sample milled for 210 min. The IC50 value decreased for samples with milling 150 and 210 min, which showed strong antioxidant activity, whereas the value of gallic acid equivalent increased. SEM observations showed the presence of agglomeration in the morphology of mangosteen pericarp samples. The average particle size of the mangosteen pericarp decreased as the milling time increased (up to 4499 nm for samples milled for 210 min). Therefore, mechanical milling had a significant effect on the phenolic content and antioxidant activity, which indicated an increase in the bioavailability of mangosteen pericarp.